WOMEN’S RIGHTS AS REFLECTED BY TARA WESTOVER IN “EDUCATED: A MEMOIR” BOOK - Fatahuddin, Sri Aminingsih; Abdullah, Abdullah (Journal of English Literature and Linguistic Studies, 2023)
Women’s rights movement aims to achieve equality with men in many aspects, including education, politics, society, economy and culture. In this research, the researcher analyzes a book titled Educated written by an American girl, Tara Westover. The purpose of this research is to know how Tara Westover is treated by the family, society and culture through the women’s rights as it has been described in Educated. The research focuses on two problems: first, women’s rights experienced by the main character and the second, main character actions toward women's rights. The book carefully and accurately analyzed using the existentialist feminism theory as a response to research problem and see how women’s resistance toward inequality. The researcher describes a woman in Idaho who has not got her rights. There are some factors that cause inequality in Idaho, such as religion, society, culture and family. All those factors make the women's rights movement so limited. They don’t have the same rights as men, women always inferior and men always superior especially in family scope or in public domain. The character in this book is reflected in existentialist feminism. However, feminism is reflected in the character's survival, the struggle to move these lives into the male world (patriarchy), comfort themselves and do things that are comfortable for them.